A new highly sensitive and specific overnight combined screening and diagnostic test for primary aldosteronism. Issue 1 (July 2016) - Tsiavos, Vaios; Markou, Athina; Papanastasiou, Labrini; Kounadi, Theodora; Androulakis, Ioannis I; Voulgaris, Nick; Zachaki, Aglaia; Kassi, Eva; Kaltsas, Gregory; Chrousos, George P; Piaditis, George P
Abstract : Context: Primary aldosteronism (PA) is the most common cause of endocrine hypertension that is diagnosed following a two-step process: an initial screening test, based on the serum aldosterone-to-renin ratio (ARR), followed by a relatively laborious and time-consuming confirmatory test to document autonomous aldosterone (ALD) secretion. Objective: The aim of this study is to develop a simple overnight test for the early and definite diagnosis of PA. Patients and methods: Totally, 148 hypertensive patients underwent a fludrocortisone–dexamethasone suppression test (FDST) and the new overnight diagnostic test (DCVT) using pharmaceutical RAAS (renin–angiotensin–aldosterone system) blockade with dexamethasone, captopril and valsartan. Results: Of the 148 patients, 45 were diagnosed as having PA and they all normalized their elevated blood pressure (BP) after administration of spironolactone or eplerenone. The remaining 103 patients were considered as having essential hypertension and served as controls. Using ROC analysis, the estimated sensitivity and specificity were 91 and 100%, respectively, for the post-FDST ARR, whereas 98% and 89% and 100% and 82% for the post-DCVT ARR and post-DCVT ALD, respectively, with selected cutoffs of 0.32ng/dL/μU/mL and 3ng/dL respectively. However, considering these cutoffs simultaneously, the estimated sensitivity and specificity were 98 and 100% respectively. Applying these cutoffs, the diagnosis of PA was confirmed in 44 (98%) of the 45 patients who were considered to have the disease. Conclusions: In this study, a highly sensitive and specific, low-cost, rapid, safe, and easy-to-perform diagnostic test (DCVT) for PA is described, which could be utilized on an outpatient basis potentially substituting conventional laborious testing.